Cr3+ doped nanoporous anodic alumina: Facile microwave assisted doping to realize nanoporous ruby and phase dependent photoluminescence. Issue 9 (15th June 2019) - Choudhari, K.S.; Hebbar N, Deepak; Kulkarni, Suresh D.; Santhosh, C.; George, Sajan D.
Abstract : Microwave-assisted solution technique (MAST) was used for the homogeneous doping of Cr 3+ in nanoporous anodic alumina (NAA) which when heat-treated transforms into nanoporous ruby. The rise in annealing temperature led to the phase transition in the sequence: amorphous- δ- θ- α-alumina as evidenced by XRD. The dopant was homogenously distributed as seen from the elemental mapping and the Cr 3+ content was 0.5 at%. Diffuse reflectance spectroscopy (DRS) displayed the characteristic blue and green absorption bands and the color-tone varied from light-green at 700 °C to the pink appearance at 1350 °C owing to the dopant diffusion. Two broad photoluminescence (PL) excitation bands centered at ∼550 nm and ∼400 nm were observed whose intensity increased with the annealing temperature. All the alumina phases exhibited characteristic phase dependent PL showing variation in the luminescence intensity and peak position. The characteristic R-line for α-phase was intense and observed at 694 nm with 4 m s lifetime in accordance with that expected for Ruby. Crystal field parameters were obtained from the PL excitation spectra and Dq/B values were found to be higher than 2.3 for all the phases of NAA confirming the presence of Cr 3+ ions in the strong crystal field. With annealing, the CIE coordinates moved towards the red region. The presented work shows a promising easy and inexpensive method for dopant incorporation into alumina and explores the understanding of phase-dependent emission of Cr 3+ doped NAA for their potential applications in the areas of nano-optics and composite luminescent nanomaterials.